meningkatkan kesabaran dan kemandirian anak sekolah dasar kelas satu di SD RENGAS PITU Kelurahan SP Padang melalui metode belajar langsung di lapangan - Khusnul Khotimah; Hazmi Azyati Zea; Lutpi Fitrianti (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Abstract The community service program in the form of education is based on collaboration between Real Work Lecture students at Raden Fatah State Islamic University, Palembang and Sp Padang District, Oki Regency, South Sumatra Province to carry out learning to train patience and independence for elementary school children at RENGAS PITU Elementary School through the method learn directly in the field. The aim of implementing the direct learning method in the field for young children is to train their patience in resisting their less important desires and to train their independence in dealing with problems that children face when interacting with people in the field. This learning method is very useful for children in their future lives so that children can mingle with society directly and understand life in the child's environment. Keywords: Patience. Independence, Direct Learning Methods and Early Childhood